Transformacja sufiksów w nazwiskach rejestrowanych współcześnie w Polsce na przykładzie formantu -uk/-czuk - Tichoniuk, Bazyli (Acta Polono-Ruthenica, 2004)
Among 10 599 surnames ending in -uk /-czuk and registered in the territory of Poland the names which filled this group as the result of the transformation of the ending part of antroponym include more than 10,60% (1127). The greatest number 87,40 % Constitute the transformation in the suffix structure - -uk /-yk, -ek and -ok, in which instead of the letters i, у, e and о letter и appeared. The remaining of the surnames were created as the result of missing or changing of the last letter. All these surnames are the effect of the mistakes made by clerks.